Boss-busters & sin hounds Kansas City and its Star - Haskell, Harry (University of Missouri Press, 2007)
"Haskell tells the tale of the Kansas City Star's rise and decline, taking readers into the city room and executive offices of one of the most respected American newspapers. This story includes Kansas City notables as Tom Pendergast, J.C. Nichols, Frank Walsh, William Rockhill Nelson, Henry J. Haskell and Roy A. Roberts"--Provided by publisher.